2023
DOI: 10.3389/fphar.2023.1111218
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect and mechanism of parthenolide in skeletal disease, cancers, and cytokine storm

Abstract: Parthenolide (PTL or PAR) was first isolated from Magnolia grandiflora and identified as a small molecule cancer inhibitor. PTL has the chemical structure of C15H20O3 with characteristics of sesquiterpene lactones and exhibits the biological property of inhibiting DNA biosynthesis of cancer cells. In this review, we summarise the recent research progress of medicinal PTL, including the therapeutic effects on skeletal diseases, cancers, and inflammation-induced cytokine storm. Mechanistic investigations reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…Our RNA sequencing results indicate that this mechanism may be related to a variety of signalling pathways and genes, which may form a complex network. Consistent with previous research, our RNA-seq results also suggest that PTL may influence other signalling pathways, such as the IL-17, JAK-STAT, P53 and NF-KB signalling pathways 16 , which are very hot topic in field of apoptosis and cancer. our results showed that PTL leads to tumour cell apoptosis, combined with RNA-seq results, it may affect the implementation of P53 cell apoptosis pathways.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our RNA sequencing results indicate that this mechanism may be related to a variety of signalling pathways and genes, which may form a complex network. Consistent with previous research, our RNA-seq results also suggest that PTL may influence other signalling pathways, such as the IL-17, JAK-STAT, P53 and NF-KB signalling pathways 16 , which are very hot topic in field of apoptosis and cancer. our results showed that PTL leads to tumour cell apoptosis, combined with RNA-seq results, it may affect the implementation of P53 cell apoptosis pathways.…”
Section: Discussionsupporting
confidence: 91%
“…PTL has been widely used for its anti-inflammatory and antioxidant properties and its biological effects in treating headaches, fever, and rheumatoid arthritis 16 . PTL has been studied for its inhibitory effect on NF-κB and its anticancer effects on many tumours, including breast cancer, prostate cancer, papillary thyroid carcinoma, and lung cancer 16 . A previous study indicated that PTL has minimal cytotoxicity against cancer stem cells in nasopharyngeal carcinoma 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the nature of the molecular target (s) of parthenolide and related sesquiterpene lactones is less clear; in fact, parthenolide has been described as having a “ …promiscuous bioactivity profile… ” [40]. Most studies on the molecular effects of parthenolide and related compounds focus on their impact on IkB kinases and nuclear factor kappa-B (NF-κB) and several classes of cytokines downstream of it, which may account for parthenolide’s antitumoral and anti-inflammatory properties [68,69]. Additionally, parthenolide interferes with microtubule physiology [70,71] and, intriguingly, has been proposed as an agent that promotes functional nervous tissue regeneration [72], in contrast to results obtained from our laboratory (in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Parthenolide ( Figure 2 ) is a type of sesquiterpenoid derived from the leaves and flowers of feverfew ( Tanacetum parthenium ) and is a natural compound that has been used as an herbal remedy since ancient times [ 55 ]. It has the chemical structure C 15 H 20 O 3 and a molecular mass of 248.32 g/mol [ 56 ], and causes anti-inflammatory and anticancer effects by strongly inhibiting the activity of nuclear factor kappa-B (NF-κB) [ 57 ]. NF-κB is an important transcription factor involved in cancer cell proliferation, survival, invasion, metastasis, and evasion of antitumor immunity.…”
Section: Natural Products For the Treatment Of Cancermentioning
confidence: 99%